The antioxidant and antimicrobial properties of grape pekmez (grape molasses-like syrup) and butter oil - Reza Karimi-Cheshmeh Ali; Amir Shakerian; Ebrahim Rahimi; Reza Sharafati Chaleshtori (Bihdāsht-i Mavādd-i Ghaz̠āyī)
Grape juice and butter oil are traditional ingredients in the Iranian diet. This study aimed to investigate their antioxidant and antimicrobial properties. The phenolic content and flavonoid compounds were determined using the Folin-Ciocalteu and aluminum chloride methods, respectively. Antioxidant activity was assessed by the DPPH assay, and the antimicrobial activity was evaluated by disk diffusion. The results revealed that the total phenolic content of grape juice was 27.41 mg/g (gallic acid equivalent), and the flavonoid content was 9.75 mg/g (quercetin equivalent). Both phenolic and flavonoid compounds decreased during storage. Grape juice exhibited significantly higher antibacterial activity than butter oil at similar concentrations (p < 0.05). Additionally, the inhibition zone diameter increased with higher concentrations of both substances. These findings demonstrate that grape juice and butter oil contain phenolic and flavonoid compounds with notable antioxidant and antimicrobial properties.